Oxacilin-resistant Coagulase-negative staphylococci (CoNS) bacteremia in a general hospital at São Paulo city, Brasil - D'Azevedo,P.A. (2008)
In the last decades, coagulase-negative staphylococci (CoNS), especially Staphylococcus epidermidis have become an important cause of bloodstream infections. In addition, rates of methicillin-resistance among CoNS have increased substantially, leading to the use of glicopeptides for therapy. The objective of this study was to evaluate eleven consecutives clinically relevant cases of oxacillin-resistant CoNS bacteremia in a general hospital localized in São Paulo city, Brazil. Five different species were identified by different phenotypic methods, including S. epidermidis (5), S. haemolyticus (3), S. hominis (1), S. warneri (1) and S. cohnii subsp urealyticus (1). A variety of Pulsed Field Gel Electrophoresis profiles was observed by macrorestriction DNA analysis in S. epidermidis isolates, but two of three S. haemolyticus isolates presented the same profile. These data indicated the heterogeneity of the CoNS isolates, suggesting that horizontal dissemination of these microorganisms in the investigated hospital was not frequent. One S. epidermidis and one S. haemolyticus isolates were resistant to teicoplanin and susceptible to vancomycin. The selective pressure due to the use of teicoplanin in this hospital is relevant.